SIRI’NA PACCE DALAM PENYELESAIAN KONFLIK HUKUM ADAT DALAM MASYARAKAT BUGIS MAKASSAR - Firki Anjana; Latifah Istidhamah; Manisa Adinda Delfi; Maulidia Tri Kusuma (Jurnal Humaniora & Sosial Sains, 2025)
The Bugis tribe from South Sulawesi is one of the ethnic groups in Indonesia that has a steadfastness in maintaining customary and cultural values, one of which is the philosophy of emphasizing the importance of maintaining self-esteem (siri') and caring for others (pacce), including in resolving conflicts peacefully and with dignity. This study aims to analyze the application of siri'na pacce values ​​in resolving social conflicts in the Bugis-Makassar community, focusing on the case of silariang (elopement). This study uses a descriptive qualitative method through literature study to examine various relevant written sources. The results of the study indicate that siri'na pacce is an ethical basis for resolving conflicts. The process of resolving this customary conflict prioritizes deliberation and restoration of social relations as in the abaji process. The values ​​of siri'na pacce are relevant in strengthening harmony and social justice amidst the development of national law.